2013
DOI: 10.1159/000351410
|View full text |Cite
|
Sign up to set email alerts
|

Remission of Generalized Anxiety Disorder after 6 Months of Open-Label Treatment with Venlafaxine XR

Abstract: Background: Remission has become one of the leading outcome criteria in clinical trials. Data collected by this research group assessed the rate of remission after 6 months of treatment of generalized anxiety disorder (GAD) with venlafaxine XR, to search for predictors of remission and to define how early on in treatment later remission can be predicted. Method: Two hundred sixty-eight patients with a GAD diagnosis enrolled into an open-label 6-month-treatment trial with venlafaxine XR (75-225 mg/day). Remissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Rickels et al [4] used this EPI neuroticism scale when predicting remission in patients with generalized anxiety disorder after 6 months of treatment with venlafaxine. Using a remission criterion of <8 on the Hamilton Anxiety Scale (HAM-A), it was shown that the neuroticism scale had predictive validity, as non-remitters had a significantly higher neuroticism score at treatment baseline than the remitters.…”
Section: Tablementioning
confidence: 99%
See 4 more Smart Citations
“…Rickels et al [4] used this EPI neuroticism scale when predicting remission in patients with generalized anxiety disorder after 6 months of treatment with venlafaxine. Using a remission criterion of <8 on the Hamilton Anxiety Scale (HAM-A), it was shown that the neuroticism scale had predictive validity, as non-remitters had a significantly higher neuroticism score at treatment baseline than the remitters.…”
Section: Tablementioning
confidence: 99%
“…gender, age, race, education, HAM-A), only the neuroticism scale was found to have predictive validity. The objective of the present analysis of the data set of Rickels et al [4] has been to perform an item analysis of the neuroticism scale to identify those items that produce the predictive validity.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations